The Manageability of the Educational System: Characteristics and Optimization - Elena Y. Levina; Nikolai Y. Kruglikov; Irina V. Krasina; Yuliа V. Mishina; Alina N. Lugova; Olga V. Railian; Olga V. Ruzakova; Irina Z. Shakhnina (International Review of Management and Marketing, 2016)
Modernization of education implies substantial changes in the management of educational systems and processes for the transition of educational systems to a qualitatively new state and to a higher level of functioning. The aim of the article is to describe the phenomenon of manageability of education systems, which consists in the real possibility to influence on the course of processes in order to improve their performance in a high dynamism and activity of the managed elements of the system. The basis of the research is the stakeholder approach, which establishes an increasing degree of responsibility of all agents of education for their actions within the system. The authors identified the specifics of educational systems’ manageability based on the characteristics of educational agents and the balance of their requirements and expectations. The principles of the stakeholder approach’s implementation in education are proposed, which allowed offer a way to increase the controllability of educational systems. The paper submissions can be useful for experts of education authorities, teachers of pedagogical and management profile, managers and staff of educational organizations, researchers who are involved in the manageability of educational systems and processes.